Effect of propofol, midazolam and dexmedetomidine on ICU patients with sepsis and on arterial blood gas - Ding, Jia (Exp Ther Med, 2019)
Effects of propofol, midazolam and dexmedetomidine on patients with sepsis in intensive care unit (ICU) and on arterial blood gas (ABG) were studied. In total 429 ICU patients with sepsis, admitted to Renji Hospital, School of Medicine, Shanghai Jiaotong University from May 2015 to January 2019, were selected as research subjects for a prospective analysis. All patients received basic treatment, such as anti-infection treatment, correction of shock and improvement of microcirculation. One hundred and fifty-two patients who were treated with propofol for sedation served as group A, 146 patients who were treated with midazolam for sedation served as group B, and 131 patients who were treated with dexmedetomidine for sedation served as group C. The three groups of patients were compared in terms of diastolic blood pressure (DBP), systolic blood pressure (SBP), heart rate (HR), arterial partial pressure of oxygen (PaO(2)), arterial partial pressure of carbon dioxide (PaCO(2)), cardiac troponin T (cTnT) and creatine kinase-MB (CK-MB) before and after treatment. APACHE II score was used to evaluate the sedative effects. The wake-up time of the patients, the length of ICU stay and the adverse reactions were recorded. There was no significant difference among groups A, B and C in terms of HR, SBP, DBP, PaO(2), PaCO(2), cTnT, CK-MB and APACHE II score before treatment, and SBP, DBP, cTnT and HR after treatment (P>0.050). After treatment, there was no significant difference between groups A and B with respect to CK-MB and APACHE II score (P>0.050). The wake-up time in group A was significantly longer than that in groups B and C (P<0.001). In conclusion, propofol, midazolam and dexmedetomidine are effective and safe in the sedative treatment of ICU patients with sepsis, but dexmedetomidine has the best effect on protecting blood pressure and cardiac functions, which is worthy of use in the clinic.